PENGARUH PERUBAHAN PERILAKU INDIVIDU DAN KARAKTERISTIK KEPRIBADIAN TERHADAP KINERJA PEGAWAI PADA UNIVERSITAS PGRI PALEMBANG - Rismansyah Rismansyah (Jurnal Media Wahana Ekonomika, 2011)
The changes in various dimensions of life can not be avoided, there must be the effect. Therefore changes continuously demanding individuals to always be able to adapt to their environment.This research design was used in causal research is to investigate the relationship between the number of variables, where the independent variables in the study were changes in individual behavior(X1) and personality characteristics(X2), Dependent variable is the performance of employees (Y), the purpose of this study is to determine how much influence individual behavior change and the personality characteristics to employee performance. Data sources used are primary data with questionnaire data collection method which amounts to 49 items, the population of all university employees PGRI Palembang totaling 498 people with a sample totaling 100 respondents, the analysis techniques used in this study is multiple linear regression analysis.The regression model was established based on the model summary obtained value of                  R = 0, 327, the value of coefficient of determination or R2 ( R square ) as high as 10,7 % or 11% while the rest equal to 89,3% influenced or explained by other variables not included in this study, the results of research of individual behavior changes affect employee performanie and personality characteristics influence the performance of employees, the results of research showed that personality characteristics in fluence the performance of employees at the University PGRI Palembang. Key words : changes in individual behavior, personality characteristics and performance of     employees